Analiza razkrojenega smrekovega lesa zaščitenega z biocidnim proizvodom CCB po 14 letih izpostavitve na prostem - Humar, Miha (Les (Ljubljana), 2021)
Wood in outdoor applications is exposed to abiotic and biotic factors. If we want to slow down the decay, the wood must be protected. In the past, biocidal products based on copper, chromium, and boron compounds (CCB) were one of the most important solutions for wood protection under extreme conditions. Although CCB is in practice no longer used in the EU, it can serve as a reference for the evaluation of new biocidal products. At the field test site of the Department of Wood Science and Technology, Biotechnical Faculty, an experiment has been carried out under real conditions for 14 years, in which impregnated samples are exposed to the weather according to a double-layer test. In the case of treated wood, we often find that the wood decays faster than expected. In this work we want to determine what contributes to decay based on the analysis of decayed impregnated wood from the field test site. The results show that sufficient retention and penetration of the active substances into the wood ensures the planned service life.
Keywords: CCB; decay; impregnacija; impregnation; les; lesne glive; razkroj; wood; wood inhabiting fungi; wood protection; zaščita lesa